2001
DOI: 10.1002/jnm.400
|View full text |Cite
|
Sign up to set email alerts
|

TLM for diffusion: the artefact of the standard initial conditions and its elimination within an abstract TLM suite

Abstract: SUMMARYWe demonstrate both analytically and numerically, that for the TLM algorithm for numerically solving the di!usion equation the standard initial conditions for the incident voltage pulses in terms of the initial concentration (or temperature) distribution introduce a signi"cant numerical error. We discover the origin of this error and present an alternative prescription for computing the node voltages at the "rst time step which removes this artefact and exhibits distinctly improved numerical accuracy. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It may, however, be possible to temporarily adjust the transmission coefficient over one or more time steps so that the long-term variance error is zero even if the model is initialized in the standard way. Since the initial time step in a TLM model is not consistent with the other time steps [8], altering that time step in order to achieve more accurate results will not reduce the consistency of the method. Equation (46) can be rewritten to give the variance at time step k in terms of the node voltage variance and the incident pulse distribution mean positions at any previous time step j k s…”
Section: Error Reductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It may, however, be possible to temporarily adjust the transmission coefficient over one or more time steps so that the long-term variance error is zero even if the model is initialized in the standard way. Since the initial time step in a TLM model is not consistent with the other time steps [8], altering that time step in order to achieve more accurate results will not reduce the consistency of the method. Equation (46) can be rewritten to give the variance at time step k in terms of the node voltage variance and the incident pulse distribution mean positions at any previous time step j k s…”
Section: Error Reductionmentioning
confidence: 98%
“…The analytical solution of the diffusion equation for a one-dimensional system of length with boundary conditions (0, t) = ( , t) = 0 and initial condition (x, 0) = sin( x/ )+3 sin(2 x/ ) is [8] …”
Section: Finite Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…As in the 1D case [7,8], the error introduced by this inconsistency is of the same order in Dt and Dx 2 as the discretization error of the 2-step scheme itself. From the point of view of d'Alembert's solution to the wave equation, the deeper reason for this is the fact that the initial condition (13a) belongs to the case @f=@tðx; 0Þ ¼ 0: The contradiction is resolved for the case t ¼ 1=4; where (9) reduces to the standard explicit FD scheme and the wave properties are essentially lost.…”
Section: New Formula For the First Time Stepmentioning
confidence: 95%
“…However, it has recently been observed that the usual initial conditions applied to the TLM algorithm are not consistent with its own difference scheme [7,8]. In this paper, we investigate an improved model initialization and apply it to a two-dimensional (2D) case in a TLM link-line model without stubs.…”
Section: Introductionmentioning
confidence: 97%